Art, nature and mental health: assessing the biopsychosocial effects of a 'creative green prescription' museum programme involving horticulture, artmaking and collections. (September 2020) - Thomson, LJ; Morse, N; Elsden, E; Chatterjee, HJ
Aims: To assess the biopsychosocial effects of participation in a unique, combined arts- and nature-based museum intervention, involving engagement with horticulture, artmaking and museum collections, on adult mental health service users. Methods: Adult mental health service users (total n = 46 across two phases) with an average age of 53 were referred through social prescribing by community partners (mental health nurse and via a day centre for disadvantaged and vulnerable adults) to a 10-week 'creative green prescription' programme held in Whitworth Park and the Whitworth Art Gallery. The study used an exploratory sequential mixed methods design comprising two phases – Phase 1 (September to December 2016): qualitative research investigating the views of participants ( n = 26) through semi-structured interviews and diaries and Phase 2 (February to April 2018): quantitative research informed by Phase 1 analysing psychological wellbeing data from participants ( n = 20) who completed the UCL Museum Wellbeing Measure pre–post programme. Results: Inductive thematic analysis of Phase 1 interview data revealed increased feelings of wellbeing brought about by improved self-esteem, decreased social isolation and the formation of communities of practice. Statistical analysis of pre–post quantitative measures in Phase 2 found a highly significant increase in psychological wellbeing. Conclusion: Creative green prescription programmes, using a combination of arts- and nature-based activities, present distinct synergistic benefits that have the potential to make a significant impact on the psychosocial wellbeing of adult mental health service users. Museums with parks and gardens should consider integrating programmes of outdoor and indoor collections-inspired creative activities permitting combined engagement with nature, art and wellbeing.